2021
DOI: 10.1038/s42003-021-01918-4
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic network of the last bacterial common ancestor

Abstract: Bacteria are the most abundant cells on Earth. They are generally regarded as ancient, but due to striking diversity in their metabolic capacities and widespread lateral gene transfer, the physiology of the first bacteria is unknown. From 1089 reference genomes of bacterial anaerobes, we identified 146 protein families that trace to the last bacterial common ancestor, LBCA, and form the conserved predicted core of its metabolic network, which requires only nine genes to encompass all universal metabolites. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 88 publications
8
31
1
Order By: Relevance
“…2, Table S1). More recently, and using different methods, LBCA has been reported as an anaerobic, rod-shaped cell utilising glucogenesis [84], and as rod shaped (with a diderm outer membrane), and motile [85], both studies depicting the bacterial ancestor in a very similar way to our own results.…”
Section: Resultssupporting
confidence: 81%
“…2, Table S1). More recently, and using different methods, LBCA has been reported as an anaerobic, rod-shaped cell utilising glucogenesis [84], and as rod shaped (with a diderm outer membrane), and motile [85], both studies depicting the bacterial ancestor in a very similar way to our own results.…”
Section: Resultssupporting
confidence: 81%
“…The topology of our phylogeny of the primary domains of life (Figure 6) is consistent with recent single-domain trees inferred for Archaea and Bacteria independently (Coleman et al, 2021;Dombrowski et al, 2020;Williams et al, 2017), although the deep relationships within Bacteria are only poorly resolved, with the exception of the monophyly of Gracilicutes (Figure 6). A recent analysis suggested that, among extant lineages, the metabolisms of Clostridia, Deltaproteobacteria, Actinobacteria and some Aquificae might best preserve the metabolism of the last bacterial common ancestor (Xavier et al, 2021). Assuming a universal root between Archaea and Bacteria (Dagan et al, 2010;Gogarten et al, 1989;Iwabe et al, 1989), none of these groups branch near the bacterial root in our analysis (Figure 6).…”
Section: A Phylogeny Of Archaea and Bacteria Inferred From 27 Vertically-evolving Marker Genesmentioning
confidence: 83%
“…Though the remaining chemical reactions of the core do not occur in all genomes, as auxotrophies arise recurrently in evolution, they are universal at the level of primary production, the process that has fueled all ecosystems from origins to today ( Hamilton et al, 2016 ; Martin et al, 2018 ). However, the enzymes that catalyze the reactions of the core are not universal, such that the core cannot be identified through purely genomic comparisons because (i) reactions that arose post LUCA , in particular O 2 -dependent reactions ( Dailey et al, 2017 ; Jabłońska and Tawfik, 2021 ), need to be filtered out ( Wimmer et al, 2021a ), (ii) because lateral gene transfers of recently arisen pathways have to be filtered out ( Weiss et al, 2016 ), and (iii) because the enzymes that catalyze these reactions are often unrelated across the archaeal-bacterial divide ( Sousa et al, 2013 ), suggesting independent origins of enzymatic pathways from LUCA en route to the last common ancestors of archaea ( Williams et al, 2017 ) and bacteria ( Xavier et al, 2021 ), respectively.…”
Section: Introductionmentioning
confidence: 99%